Soorte vrae in 1 Korintiërs 1–4 - Snyman, AH (Nederduitse Gereformeerde Teologiese Tydskrif, 2010)
Types of questions in 1 Corinthians 1–4 The approach in this article differs from that of traditional grammars and commentaries, where all questions are classified as either true or rhetorical, and their functions mainly described as part of the diatribe-style or as expressing vivid emotion. The identification of questions here is based on a model developed from speech act theory, which distinguishes six main and various sub-categories of non-true questions. This model is briefly summarised, followed by a systematic investigation of all the questions in 1 Cor 1–4. The conclusion is that the proposed model is useful for distinguishing various types of questions within a scientific framework and for determining their communicative functions, thereby contributing to the translation and exegesis of the passages involved.